PRAKTIK WAKAF UANG DI KSPPS BMT BAHTERA KOTA PEKALONGAN DITINJAU DARI REGULASI PERWAKAFAN UANG DI INDONESIA - guswanto, afif (Al-Hukkam: Journal of Islamic Family Law, 2023)
Waqf is an important instrument that supports the development of the people. Cash waqf is one of the innovations in waqf. Cash waqf has been regulated in detail through several regulations in Indonesia. In the city of Pekalongan there are still many practices that are not in accordance with those regulations. Most of the cash waqf practices in this region are waqf through money. The author found a financial institution in Pekalongan city that runs the practice of cash waqf that is identical to that expected by the government through the regulation of Cash waqf, namely KSPPS BMT Bahtera. Based on these descriptions, this study aims to determine how detailed the practice of Cash waqf carried out by KSPPS BMT Ark. So that it can be known the suitability of the practices carried out with the regulation of money representation applicable in Indonesia.This type of research is field research using a qualitative approach. The results of this study indicate that some of the cash waqf practices in KSPPS BMT Bahtera are in accordance with the regulation of money Waqf in Indonesia, namely in the sector of managing and utilizing cash waqf funds. However, there are some other practices that are not in accordance with the regulation of money transfer in Indonesia, namely in the administrative sector. Although there are practices that are not technically appropriate, the practice of cash waqf carried out in BMT Bahtera still meets Islamic law when viewed from the substance.